BC200 LncRNA a potential predictive marker of poor prognosis in esophageal squamous cell carcinoma patients - Zhao, Rui-Hua (Onco Targets Ther, 2016)
OBJECTIVE: To explore the expression and prognosis significance of BC200 in esophageal squamous cell carcinoma (ESCC) patients who received radical resection. METHODS: We used quantitative real-time polymerase chain reaction to detect the expression level of BC200 in cancer tissue and paired adjacent normal tissue samples from 70 ESCC patients who received radical surgical resection and analyzed the correlation of the relative expression level of BC200 with clinical-pathological features and prognosis. RESULTS: We found that the relative expression of BC200 was significantly higher in ESCC tissues compared with adjacent normal tissue samples (P=0.023). But the expression of BC200 were not related to clinical-pathological features, such as age, TNM stages, and histological grade (P>0.05). Kaplan–Meier analysis showed that high expression levels of BC200 were correlated with poor prognosis in ESCC patients. Patients with a high level of BC200 had a shorter disease-free survival and overall survival than those with low BC200 expression (P=0.034 and P=0.031, respectively). On multivariate analysis, the hazard ratio (HR) of BC200 expression was 2.17 (95% confidence interval [CI]=1.12–4.19, P=0.022) for disease-free survival and 2.24 (95% CI=1.12–4.49, P=0.023) for overall survival. CONCLUSION: Our results indicate that high expression of BC200 reflects poor prognosis and could serve as a novel predictive marker for ESCC patients who received radical resection.